2012
DOI: 10.1080/00028487.2012.720626
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wild Trout to Stream Restoration over Two Decades in the Blackfoot River Basin, Montana

Abstract: Anthropogenic degradation of aquatic habitats has prompted worldwide efforts to improve or restore stream habitats for fisheries. However, little information exists on the long‐term responses of salmonids to restoration in North American streams. To recover wild trout populations in the Blackfoot River in western Montana, a collaborative approach to stream restoration began in 1990 to improve degraded stream habitats, primarily on private land. To assess the efficacy of various restoration techniques (channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Results show that climatic changes are interacting with legacies of species introduction and habitat degradation to threaten native cutthroat trout, as invasive rainbow trout continue to expand their range. Remaining nonhybridized populations represent only a fraction of the historic distribution and genetic diversity of cutthroat trout (Allendorf & Leary, ; Shepard et al., ), underscoring the urgency of addressing invasive hybridization through proven conservation strategies (e.g., suppression of non‐natives, installation of barriers, habitat restoration and protection) that prevent genomic extinction of additional populations and eventually entire lineages (Al‐Chokhachy et al., ; Muhlfeld et al., ; Pierce, Podner, & Carim, ). More broadly, our results suggest that mitigation of chronic human stressors—translocation of species and habitat modification—that interact with climate to promote the expansion of invasive species will be crucial for conserving biodiversity (Hauer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Results show that climatic changes are interacting with legacies of species introduction and habitat degradation to threaten native cutthroat trout, as invasive rainbow trout continue to expand their range. Remaining nonhybridized populations represent only a fraction of the historic distribution and genetic diversity of cutthroat trout (Allendorf & Leary, ; Shepard et al., ), underscoring the urgency of addressing invasive hybridization through proven conservation strategies (e.g., suppression of non‐natives, installation of barriers, habitat restoration and protection) that prevent genomic extinction of additional populations and eventually entire lineages (Al‐Chokhachy et al., ; Muhlfeld et al., ; Pierce, Podner, & Carim, ). More broadly, our results suggest that mitigation of chronic human stressors—translocation of species and habitat modification—that interact with climate to promote the expansion of invasive species will be crucial for conserving biodiversity (Hauer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A review of published studies evaluating the physical and biological effectiveness of restoration projects found 345 published studies representing dozens of techniques; however, more than half of these studies focused on instream habitat improvement ). Most studies focused on a specific stream, project, or site (e.g., Cederholm et al 1997;Reeves et al 1997; but see Pierce et al 2013), and many restoration techniques, such as floodplain enhancement, riparian planting, and invasive species removal and even barrier removal, have not been comprehensively monitored . Some studies have reported on the effectiveness of particular techniques by doing retrospective analysis (e.g., Roni and Quinn 2001;Louhi et al 2011) rather than analysis of detailed before and after monitoring data.…”
mentioning
confidence: 98%
“…In fact, many studies report large (>50%) and significant increases in pool frequency, pool depth, woody debris, habitat heterogeneity, complexity, spawning gravel, or sediment and organic matter retention following placement of instream structures, particularly in mountain streams and rivers (e.g., Binns 1999; Brooks et al 2004;Cederholm et al 1997;Gerhard and Reich 2000;Pierce et al 2013;Reeves et al 1997;Roni and Quinn 2001a). Studies in low-gradient (<1.5%) streams such as those in the US Midwest or western Europe have demonstrated physical habitat changes, including increased depth, cover, narrower channels, and increased organic matter retention, as a result of wood placement projects (e.g., Gerhard and Reich 2000;Hunt 1988;Laitung et al 2002;Zika and Peter 2002).…”
Section: Physical Response To Wood Placementmentioning
confidence: 99%